Reducing EFL Learners’ Speaking Anxiety through Selective Error Correction and Group Work - Zulfikar Zulfikar (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
This quantitative study aimed to examine the level of speaking anxiety experienced by second-year high-school Acehnese EFL learners in their oral performance in L2 classroom and to investigate the attempt to lower their anxiety through the implementation of selective error correction and group work. The Foreign Language Speaking Anxiety Scale (Horwitz et al., 1986) was used as a means to survey and evaluate the learners’ speaking anxiety, and their oral performance was assessed through speaking performance rubric as adopted from Ismailia (2021) before and after the learners’ exposure to selective error correction and group work. The findings showed that a high level of speaking anxiety was found in the majority of the learners, and that the use of selective error correction and group work for the treatment of speaking anxiety overall resulted in the learners’ improved performance in their oral task. The findings highlighted the needs to create a positive and supportive educational environment that stimulates learners to freely experiment with L2 and to establish close-knit learning communities that promote authentic interactions in L2 and provide opportunities to be more engaged in oral language use.